2003
DOI: 10.1200/jco.2003.06.132
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Twice-Weekly Paclitaxel With Concurrent Radiation Therapy Followed by Surgery and Postoperative Doxorubicin-Based Chemotherapy in Locally Advanced Breast Cancer: A Phase I/II Trial

Abstract: Twice-weekly paclitaxel with concurrent RT is a feasible and effective primary treatment for LABC. Future studies should compare primary chemoradiation to chemotherapy in LABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 27 publications
4
73
1
3
Order By: Relevance
“…Brackstone et al [8] in this first clinical trial evaluating concurrent neoadjuvant CCRT with a taxane as part of a modern chemotherapy regimen (FEC-D), support the same findings of the Formenti group. He suggests that this regimen significantly improved the PCR rate in LABC patients; however, the benefit shown in DFS and OS at 3 years was not statistically significant when compared with a propensity-matched control group.…”
Section: Abscopal Effects Of Radiation Therapysupporting
confidence: 71%
See 3 more Smart Citations
“…Brackstone et al [8] in this first clinical trial evaluating concurrent neoadjuvant CCRT with a taxane as part of a modern chemotherapy regimen (FEC-D), support the same findings of the Formenti group. He suggests that this regimen significantly improved the PCR rate in LABC patients; however, the benefit shown in DFS and OS at 3 years was not statistically significant when compared with a propensity-matched control group.…”
Section: Abscopal Effects Of Radiation Therapysupporting
confidence: 71%
“…In the other hand Formenti et al [8] has concluded that toxicities can be considerably reduced if paclitaxel is administered twice weekly at 30 mg/m 2 as an alternative of weekly at 80 mg/m 2 or as a continuous infusion at 20-30 mg/m 2 daily. Moreover, update data demonstrated that pathological response was higher and was associated with better disease-free survival (DFS) and overall survival OS when compared with non-responders within the same treatment cohort [8].…”
Section: Abscopal Effects Of Radiation Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…С другой стороны -может при-вести к развитию серьезных осложнений. В литературе к настоящему моменту представлены данные различных исследований по безопасности и эффективности как па-раллельного [4,5,6,7], так и последовательного приме-нения химиолучевой терапии [8,9,10]. Помимо этого, активно изучается радиочувствительность опухолей, обладающих гиперэкспрессией HER2 / neu [11].…”
Section: Introductionunclassified